Predictive power of a body shape index and traditional anthropometric indicators for cardiovascular disease: a cohort study in rural Xinjiang, China - Tao Wu; Bin Wei; Yan-peng Song; Xiang-hui Zhang; Yi-zhong Yan; Xin-ping Wang; Jiao-long Ma; Mulatibieke Keerman; Jing-yu Zhang; Jia He; Ru-lin Ma; Heng Guo; et al. (Taylor & Francis Group, 2022)
Background A body shape index (ABSI) has been proven to be related to a population's CVD incidence. However, the application of this indicator has produced different results. Aim This study aimed to evaluate the applicability of the ABSI in predicting the incidence of CVD in rural Xinjiang, China, and compare it with waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), and body mass index (BMI). Subjects and methods 5375 people aged 18 years or older were included in the study. We used the Cox proportional hazard model to evaluate the relationship between WC, WHR, WHtR, BMI, and ABSI and the incidence of CVD, the area under the curve (AUC) to evaluate the predictive power of each anthropometric index for the incidence of CVD, and restricted cubic splines are used to analyse the trend relationship between anthropometric indicators and the incidence of CVD. Results After multivariate adjustment, standardised WC, WHR, WHtR, BMI, and ABSI all positively correlated with the incidence of CVD. WC had the highest HR (95% CI) value, 1.64 (1.51-1.78), and AUC (95% CI) value, 0.7743 (0.7537-0.7949). ABSI had the lowest HR (95% CI) value, 1.21(1.10-1.32), and AUC (95% CI) value, 0.7419 (0.7208-0.7630). In the sex-specific sensitivity analysis, the predictive ability of traditional anthropometric indicators for the incidence of CVD is higher than that of ABSI. Conclusions In the rural areas of Xinjiang, the traditional anthropometric indicators of WC had better ability to predict the incidence of CVD than ABSI.